2019
DOI: 10.1016/j.ebiom.2019.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Mucin O-glycans facilitate symbiosynthesis to maintain gut immune homeostasis

Abstract: BackgroundThe dysbiosis of gut microbiota has been implicated in the pathogenesis of inflammatory bowel diseases; however, the underlying mechanisms have not yet been elucidated. Heavily glycosylated mucin establishes a first-line barrier against pathogens and serves as a niche for microbial growth.MethodsTo elucidate relationships among dysbiosis, abnormal mucin utilisation, and microbial metabolic dysfunction, we analysed short-chain fatty acids (SCFAs) and mucin components in stool samples of 40 healthy sub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 88 publications
2
51
0
Order By: Relevance
“…This identified significant positive correlations between glycans terminating with Neu5Ac (N) and two SCFAs, acetate, and butyrate (Pearson correlation = 0.55 and 0.36, respectively). Colonic mucin O -glycans have been proposed to regulate the production of SCFAs, 47 , 48 specifically the biosynthesis of butyrate. 47 However, these previous studies were limited to quantifying the total mucin proteins and O -glycans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This identified significant positive correlations between glycans terminating with Neu5Ac (N) and two SCFAs, acetate, and butyrate (Pearson correlation = 0.55 and 0.36, respectively). Colonic mucin O -glycans have been proposed to regulate the production of SCFAs, 47 , 48 specifically the biosynthesis of butyrate. 47 However, these previous studies were limited to quantifying the total mucin proteins and O -glycans.…”
Section: Resultsmentioning
confidence: 99%
“…Colonic mucin O -glycans have been proposed to regulate the production of SCFAs, 47 , 48 specifically the biosynthesis of butyrate. 47 However, these previous studies were limited to quantifying the total mucin proteins and O -glycans. Our study provides further insight and demonstrates an association between specific mucin O -glycan structures and the concentrations of acetate and butyrate.…”
Section: Resultsmentioning
confidence: 99%
“…In early life, appropriate intestinal colonization by specific microflora stimulates maturation of the intestinal mucosa-associated lymphoid tissue (6). Should the appropriate intestinal flora fail to form during this life stage, the function of the intestinal immune system becomes impaired, leading to increased incidence and/or morbidity of certain intestinal diseases, including ulcerative colitis, Crohn's disease, and colorectal cancer (7,8). In addition, activation of the immune system in the intestinal region depends on expression of pathogen-associated molecular patterns (PAMPs), e.g., intestinal microbial products.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that animals that are fed mucin show higher fecal butyrate levels. This compound is an anti-inflammatory SCFA considered positive for health and significantly decreased in inflammatory diseases such as Ulcerative Colitis (UC; Chen et al, 2018;Yamada et al, 2019). In UC subjects, mucin O-glycan abundance correlates negatively with butyrate production in feces, showing a reduced utilization of O-glycans by the gut microbiota (Yamada et al, 2019).…”
Section: O-linked Glycans From Mucinmentioning
confidence: 99%
“…Yamada et al (2019) reported that fermentation of mucin O-glycans is associated with the production of butyrate in healthy subjects. However, subjects with UC show altered mucin O-glycosylation patterns, and the abundance of A. muciniphila was inversely proportional to the markers of inflammation (Earley et al, 2019;Yamada et al, 2019). This suggests that the O-glycosylation patterns present in mucins influence the anti-inflammatory activity of certain commensal microorganisms.…”
Section: Utilization Of O-linked Glycans By Verrucomicrobiamentioning
confidence: 99%